Social Policy and Religion in a Globalizing Era - Dan, Adrian-Nicolae; Stănescu, Nina (Technium Social Sciences Journal, 2023)
Our paper critically analyses the well-known and old partnership between religious actors and social policy agencies undertaking interventions in the public sphere aimed at influencing redistributive measures (social welfare, distributive justice) and development. Starting from a typology of religious welfare and classic welfare regime the paper underlines the necessity of rising up further the "social mission of religion" in a globalized world increasingly exposed to social, economic and political turbulence, as a link between state and community.